Pengembangan Produk Keripik Singkong Industri Rumah Tangga terhadap Analisis Perspektif Konsumen - Nofriani Fajrah; Arsyad Sumantika (Prosiding, 2022)
SME that arise from the impact of decreasing job opportunities in the industry, one of which is the food industry such as snacks, drinks and even other forms of food products. This is indicated by the product produced still not paying attention to product quality from the organoleptic side of the product. Organoleptic aspects that are usually analyzed from a product are color, aroma, texture and appearance. The purpose of this research is to identify the potential of home industry cassava chips product development based on consumer perspective analysis. This study will show differences in the position of the quality attribute of cassava chips based on the distribution of chips in Batam (Brand X, Brand Y, and Brand Z). Based on the research that has been done, it is known that X cassava chips have superior taste, color and flavor variants, Y cassava chips are superior in terms of aroma, shape, and texture, and Z cassava chips are superior in size, price, and nutritional content.